2012
DOI: 10.1109/jsen.2011.2166114
|View full text |Cite
|
Sign up to set email alerts
|

Automotive FDS Resolution Improvement by Using the Principle of Rational Approximation

Abstract: In this paper, a novel method of frequency counting of signals coming from automotive sensors is presented. The present method helps to improve fast resolution of output parameters of typical automotive frequency-domain sensors (FDS). Controlling the electromechanical systems in today's cars is a task that requires a high processing speed. The method proposed here has been tested under computer experiments, and theoretical results have shown that it meets the requirements of speed of response and offset error … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Applications for SAW sensors focused on detecting pressure or force changes, which allows to make force sensors and very sensitive weighing devices; typical operating frequencies are in the order of hundreds of hertz. For the automotive industry are used SAW sensors for pressure sensing in engine test cells [16] or as torque sensors [17]; for chemical compound detection the SAW based device is modified with a sensitive material to the analyte to be detected; the use of polymer coated SAW sensor arrays combined with solid phase microextraction was used for quality control using a micronose for differentiation between apple varieties, ripe and unripe pineapple and detection of an off flavor in sugar [18]; a polymer coated surface SAW sensor for detection of buried/hidden explosives [19].…”
Section: Surface Acoustic Wave (Saw) Sensorsmentioning
confidence: 99%
“…Applications for SAW sensors focused on detecting pressure or force changes, which allows to make force sensors and very sensitive weighing devices; typical operating frequencies are in the order of hundreds of hertz. For the automotive industry are used SAW sensors for pressure sensing in engine test cells [16] or as torque sensors [17]; for chemical compound detection the SAW based device is modified with a sensitive material to the analyte to be detected; the use of polymer coated SAW sensor arrays combined with solid phase microextraction was used for quality control using a micronose for differentiation between apple varieties, ripe and unripe pineapple and detection of an off flavor in sugar [18]; a polymer coated surface SAW sensor for detection of buried/hidden explosives [19].…”
Section: Surface Acoustic Wave (Saw) Sensorsmentioning
confidence: 99%
“…The frequency measurement principle of rational approximation was proposed by Sergiyenko-Hernandez (Hernández Balbuena et al, 2009), applications for the FDS in the industries also have been proposed based on this method (Molina, 2013;Murrieta R et al, 2010;Sergiyenko et al, 2012), and it has shown important advantages over other frequency measurement techniques (Johansson, 2005). Among these improvements are invariance to timing jitter and the fact that uncertainty of the measurement does not depend on the time of measurement.…”
Section: Measurement Processmentioning
confidence: 99%
“…The frequency measurement principle of rational approximation was proposed by Sergiyenko-Hernandez [13], applications for the FDS in the automotive and aviation industries also have been proposed based on this method and it has shown important advantages over other frequency measurement techniques [14], [15], [16]. Among these improvements are invariance to timing jitter and the fact that uncertainty of the measurement does not depend on the time of measurement.…”
Section: Rational Approximationmentioning
confidence: 99%